Incidence and risk factors of age-related macular degeneration in patients with Parkinson’s disease: a population-based study - Yoon, Bora; Sa, Ho-Seok; Kim, Hwa Jung (Frontiers in Aging Neuroscience, 2024)
Background and objective The association between age-related macular degeneration (AMD) and Parkinson’ disease (PD) remains unclear. The aim of the present study was to assess the incidence of AMD in patients with PD, elucidate differences by age and sex, and investigate potential risk factors for AMD. Methods Data were extracted from the Korean National Health Insurance System database, which covers 97% of the Korean population (2002 through 2019). We calculated the incidence of newly diagnosed AMD in patients with PD and used Cox proportional-hazards models to estimate risk factors for AMD, presenting adjusted hazard ratios (aHR) with 95% confidence intervals (CI). Results Of 172,726 patients with PD, 15,800 were newly diagnosed with AMD during the follow-up, including 5,624 men and 10,176 women. The overall incidence of AMD in patients with PD was 13.59 per 1,000 person-years. Stratified by age group and sex, the incidence was higher in women aged 40–69, and conversely higher in men aged 70–89. Risk of AMD was high in older age groups (aHR = 4.36, 95% CI: 3.74–5.09 in the 70 s), female sex (aHR = 1.07, 95% CI: 1.04–1.11), patients with diabetes mellitus (DM) (aHR = 1.14, 95% CI: 1.10–1.18), and patients with hyperlipidemia (aHR = 1.17, 95% CI: 1.13–1.21). Conclusion Our findings suggest that the AMD incidence is higher in patients with PD than in the general population, with varying patterns of sex differences across age groups. Particularly, old age, female sex, presence of DM, and hyperlipidemia are potential risk factors. Therefore, clinicians should pay greater attention to AMD in patients with PD.